Total Quality Management dan Kinerja Organisasi - Murni, Murni; Sari, Dwi Alpita; Jarista, Linda; Wulandari Wulandari; Nugroho, Novrian Cahyo (Journal of Student Research, 2024)
The purpose of this study is to conduct a literature review of previous research on Total Quality Management (TQM) from 2020-2024. This research uses SLR which presents quantitative data on TQM issues and organizational performance. There are several measurements used, namely journals, variables, and theories and fields of research approaches. The results showed 31 articles from accredited national journals and national journals. The topic of college performance is influenced by variables of information technology, quality assurance, financial perspective, growth learning perspective, customer perspective, internal perspective, the theory used is TQM theory. The field of management accounting in universities and private universities has researched a lot about TQM. Only a few non-profit organizations use TQM. Based on TQM measurements that are widely used are financial and customer perspectives. Although the college has successfully implemented TQM, the main challenge faced is the alignment of key performance indicators and the college's long-term goals. This research provides insights, benefits, and barriers in implementing and recommending TQM to improve organizational performance.